2021
DOI: 10.1093/ibd/izab136
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Predict Clinical Recurrence of Inflammatory Bowel Disease

Abstract: Background Inflammatory bowel disease (IBD) patients are at high risk for depression, and depression has been shown to affect disease course. We examined interrelations between depression, genetic risk factors for depression, and IBD flares. Method In 1973 patients (1137 Crohn’s disease, 836 ulcerative colitis) of the Swiss IBD Cohort Study (SIBDCS), depressive status (hospital anxiety and depression subscale for depression, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 73 publications
(85 reference statements)
1
23
0
Order By: Relevance
“…However, many of these studies have not characterized patients based on presence or absence of disease activity at baseline. [15][16][17]36 In one study that restricted recruitment to patients with IBD in remission, a significant increase in risk of flare of disease activity and escalation was seen in those with symptoms of common mental disorders at baseline. 4 In other studies of similar design, stress also appears to be a predictor of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these studies have not characterized patients based on presence or absence of disease activity at baseline. [15][16][17]36 In one study that restricted recruitment to patients with IBD in remission, a significant increase in risk of flare of disease activity and escalation was seen in those with symptoms of common mental disorders at baseline. 4 In other studies of similar design, stress also appears to be a predictor of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that people with comorbid anxiety and depression in IBD could benefit from non-pharmacologic interventions, yet often did not have access to interventions ( Dubinsky et al, 2021 ). In a longitudinal study, Jordi et al (2021) found that depression at enrollment was a robust risk factor for more severe IBD disease and inflammatory activity over time. Additionally, reduced depressive symptoms are associated with many health behaviors such as medication adherence, healthy diet, exercise, access to social support, and other behaviors that contribute to positive disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The patients got CDAI ≥ 150 [ 17 ] or simplified endoscopic activity score for Crohn’s disease (SES-CD) [ 18 ] ≥ 2 during the follow-up period within 1 year. (2) Any CD-related hospitalization, surgery, need for rescue corticosteroids, and treatment dose escalation within 1 year [ 4 , 19 , 20 ]. As long as one of the above conditions occurred, the patient was considered to have recurrence.…”
Section: Methodsmentioning
confidence: 99%